Clutch time : a shot clock novel - Butler, Caron, 1980-; Reynolds, Justin A. (Butler, Caron, 1980- Shot clock novel, 2024)
"Kofi "KO" Douglas knows how to handle pressure. After all, he is the newly announced #1 ranked AAU player in the country. On the court, his game is as good as it gets--even if his Wolves team lost to the Sabres in the national championship, KO always believes nobody can beat him one-on-one. That is, until his former best friend, Ripp, returns home, just in time for the biggest tournament of the summer, the McNabby. Ripp's dad plays professional basketball overseas, and Ripp has been tearing up courts there--KO now has his toughest competition yet. As KO gears up for this latest challenge, there's game-changing news at home. KO's dad, who has been incarcerated for the last seven years, is getting out. It's been KO and his mom for as long as he can remember, only now his dad is ready to reconnect. It's another reunion KO isn't sure he wants to happen, especially as Ripp keeps calling out KO to play him in the McNabby. With the tournament on the horizon, KO decides to turn to Coach James and the Sabres for help. He may not love the idea of playing with Tony Washington and his former teammates again, but he needs them now more than ever. Can KO prove he's still the best on the court as his family life turns upside down?